A Novel Hybrid MCDM Approach for Complicated Supply Chain Management Problems in Construction. (2017) - Tamošaitienė, Jolanta; Zavadskas, Edmundas Kazimieras; Šileikaitė, Inga; Turskis, Zenonas
Abstract: The paper tackles a hybrid multi-criteria decision-making (MCDM) model related to supply chain management, problems, and the supplier selection problem. Modern management of materials and products requires continuous evaluation of numerous complex social, ecological, and economic factors. A group decision process using Analytic Hierarchical Process (AHP) approach presented to find the criteria weights. Measurement of conflict among criteria and decision makers presented with illustration and numerical example. Firstly, eight evaluation criteria, including cost, quality, distance, and delivery, reliability, reputation, and technology level, compatibility, and development ability identified. Later, the ARAS and the Multiplicative Utility function adopted for ranking and selecting suppliers. Criteria values normalized according to Hovanov method. The ARAS method with this normalisation method named as a hybrid original model INMUARAS.